CO-SHOPPER, MALL ENVIRONMENT, SITUATIONAL FACTORS EFFECTS ON SHOPPING EXPERIENCE TO ENCOURAGE CONSUMERS SHOPPING MOTIVATION - Wulandari, Gusti Ayu; Suryaningsih, Ika Barokah; Abriana, Roshinta Meta (Universitas Brawijaya, Indonesia, 2021)
Motivation at a shopping Centres can be influenced by a pleasant shopping experience caused by other factors such as the role of companion, the shopping environment, and other situational factors. This study aims to determine the effect of co-shoppers, shopping environment, situational factors on shopping motivation through shopping experience in Jember Shopping Centres in the Covid-19 pandemic era. The population in this study are consumers who shop in all shopping Centres in Jember. The research sample is 125 respondents who are deemed sufficient to meet the requirements of the PLS analysis method of this study with purposive sampling methods. The results showed that the coshopper had no significant effect on the shopping experience; the shopping environment has a significant positive effect on the shopping experience; situational factors have no significant effect on the shopping experience. Co-shopper has a significant positive effect on shopping motivation. The shopping environment has no significant effect on shopping motivation. Situational factors have a significant positive effect on shopping motivation, and the Shopping Centre's shopping experience has a significant positive effect on shopping motivation. Shopping Centres managers need to create an attractive and comfortable shopping environment to provide a pleasant shopping experience. Meanwhile, to increase shopping motivation, managers need to consider creating a comfortable atmosphere for coshoppers and creating co-conducive situational factors in increasing consumer shopping motivation in the shopping Centres they lead.